Vaccine justice and bioethical reflections of COVID-19 immunization in Malaysia - Moorthy, Ravichandran; S. Gill, Sarjit; Selvadurai, Sivapalan; Gurunathan, Angelina (MDPI, 2022)
Malaysia has the highest infection rate in Southeast Asia, with over 1 million positive COVID-19 cases and over 8500 deaths. The National Immunization Programme, which began in late February 2021, had a particularly slow vaccination rate, with only 4% of the targeted group receiving vaccination in three months. The delay has sparked a lot of public debate and concern, especially in light of allegations of vaccine injustice, unclear prioritization, queue jumping by people in positions of power, and other aspects of the vaccination process. Using an interpretative social science approach, this paper examines the ethical issues that arise in Malaysia’s COVID-19 vaccination discourse, focusing on vaccine justice and the bioethical principle of ‘respect for autonomy’. The paper finds that despite several shortfalls in the immunization process, most Malaysians remain optimistic and support the government’s immunization initiatives. The paper contributes to the understanding that building public trust is critical to the success of the immunization programme. Health agencies should make more efforts to inform the public about the benefits and risks of vaccines, as well as the transparency of immunization processes, which will increase public trust in health systems.